1996
DOI: 10.1111/j.1476-5381.1996.tb16085.x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of α2‐adrenoceptor agonists on gastrointestinal transit during croton oil‐induced intestinal inflammation

Abstract: 1 The peripheral effects of a2-adrenoceptor agonists were investigated in a model of intestinal inflammation induced by intragastric administration of croton oil (CO). Our

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Croton oil is a well known irritant that has been widely used to produce experimental inflammation in different tissues, especially skin and mucosa, and induces diarrhoea associated with intestinal inflammation in the mouse small intestine (Pol et al ., 1996). According to Pol et al ., (1996), we have shown that croton oil increases upper gastrointestinal transit 3 h after oral administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Croton oil is a well known irritant that has been widely used to produce experimental inflammation in different tissues, especially skin and mucosa, and induces diarrhoea associated with intestinal inflammation in the mouse small intestine (Pol et al ., 1996). According to Pol et al ., (1996), we have shown that croton oil increases upper gastrointestinal transit 3 h after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Croton oil is a well known irritant that has been widely used to produce experimental inflammation in different tissues, especially skin and mucosa, and induces diarrhoea associated with intestinal inflammation in the mouse small intestine (Pol et al ., 1996). According to Pol et al ., (1996), we have shown that croton oil increases upper gastrointestinal transit 3 h after oral administration. The cannabinoid agonists WIN 55,212‐2 and cannabinol blocked the increase in intestinal motility induced by croton oil; in addition, the ED 50 values of i.p.‐injected WIN 55,212‐2 and cannabinol were significantly decreased (compared to control mice).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute inflammation was induced by the intragastric administration of 0.05 ml of croton oil (CO) according to the method described previously (Pol et al , 1994; 1996b). Two other groups of animals receiving the same volume of saline (SS) or castor oil (CA) served as controls (Pol et al , 1996c). All groups of animals were weighed and placed into separate cages.…”
Section: Methodsmentioning
confidence: 99%
“…In different animal models, peripheral inflammation induces a 'sensitization' of opioid and · 2 -adrenergic receptors, enhancing the effects of exogenously administered agonists [5][6][7][8]. In the present investigation our working hypothesis was that during inflammation, encapsulated morphine would preserve the enhanced antinociceptive effects manifested by the free form, while showing a longer duration of action; thus, effective and long-lasting analgesia should be obtained with lower doses of MS-LP than MS-F.…”
Section: Introductionmentioning
confidence: 99%